(untitled) (Third Sector Social Economic Review, 2024)
Within the scope of the research, it is aimed to determine the mediating role of organizational inertia perception in the effect of power distance perceptions of aviation sector employees on their alienation levels. For this purpose, a questionnaire was applied to 396 participants working in the aviation sector across Turkey. In the questionnaire form, there are 4 sections including demographic information form, Organizational Power Distance Scale, Organizational Inertia Scale and Job Alienation Scale. SPSS 26.00 and Smart PLS 4 software were used to analyze the data. In the analysis, reliability and validity tests were conducted to evaluate the structural model. In the evaluation phase of the measurement model, the research hypotheses were tested with the established structural equation model. According to the findings of the study, perceived power distance increases the level of alienation from work together with employee perceptions of insight inertia, action inertia and psychological inertia. In addition, it was determined that the perception of action inertia and psychological inertia among the factors related to organizational inertia increased alienation from work. According to the results of the analysis conducted to test the indirect effects, the mediating roles of action inertia and psychological inertia perceptions were seen separately in the effect of power distance perception on job alienation.